First observations of B[bar]0s → D+D−, D+sD− and D0D[bar]0 decays - Aaij, Roel; Aquines Gutiérrez, Osvaldo; Bachmann, Sebastian; Bien, Alexander; Blouw, Johan; Britsch, Markward; Di Canto, Angelo; Dordei, Francesca; Färber, Christian; Fontana, Marianna; Gersabeck, Evelina; Grünberg, Oliver; et al. (Physical review. D, Particles, fields, gravitation, and cosmology, 2021)
First observations and measurements of the branching fractions of the B̄0s→D+D−, B̄0s→D+sD− and B̄0s→D0D̄0 decays are presented using 1.0 fb−1 of data collected by the LHCb experiment. These branching fractions are normalized to those of B̄0→D+D−, B0→D−D+s and B−→D0D−s, respectively. An excess of events consistent with the decay B̄0→D0D̄0 is also seen, and its branching fraction is measured relative to that of B−→D0D−s. Improved measurements of the branching fractions B(B̄0s→D+sD−s) and B(B−→D0D−s) are reported, each relative to B(B0→D−D+s). The ratios of branching fractions are B(B̄0s→D+D−)B(B̄0→D+D−)=1.08±0.20±0.10, B(B̄0s→D+sD−)B(B0→D−D+s)=0.050±0.008±0.004, B(B̄0s→D0D̄0)B(B−→D0D−s)=0.019±0.003±0.003, B(B̄0→D0D̄0)B(B−→D0D−s)<0.0024 at 90% CL, B(B̄0s→D+sD−s)B(B0→D−D+s)=0.56±0.03±0.04, B(B−→D0D−s)B(B0→D−D+s)=1.22±0.02±0.07, where the uncertainties are statistical and systematic, respectively.